Properties of Microsomal Activator of Profibrinolysin Found in Bovine and Porcine Heart Muscle - Nakahara, M; Celander, D. R (Thrombosis and Haemostasis, 1968)
Mitochondrial, lysosomal, and microsomal fractions of pig and cow myocardial cells were screened for their ability to effect lysis of bovine fibrin plates prepared with Profibrinolysin-containing and profibrinolysin-free reagents. Little if any activity was observed on profibrinolysin-free fibrin plates. Maximum activity on Profibrinolysin-containing plates was found in association with the microsomes. Extraction of the microsome preparations with 0.15 M KCl and 2.0 M KCl dissolved activator molecules with different pH solubility and stability characteristics. The activator activity of the 2.0 M KCl extract was in general more stable to acid pH than that of the 0.15 M KCl extract.The activator characteristic of the microsomal suspensions and of both types of microsome extracts was stable to acetone precipitation. However, the 2.0 M KCl extract lost its relatively greater stability to acid pH when precipitated with acetone. The significance of the chemical environment as a determining factor in final properties of purified enzyme molecules is discussed. The importance of using a relatively homogeneous cell population as starting material is also emphasized.